PENGARUH KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASAIONAL DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOUR (Studi pada Kantor Pusat Universitas Udayana) - Sudarmayasa, I Gede Agus; Sintaasih, Desak Ketut; Riana, I Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.11.TAHUN 2016, 2016)
Organizational citizenship behaviour is the behavior of the extra that are not part of the formal obligations of an employee's work, but support the functioning of the organization effectively. This study aimed to analyze the effect of job satisfaction on organizational commitment and Organizational citizenship behaviour. This research was conducted at the office of the Rector of Udayana University using sample that 57 non-government employees. Data were collected by interviews and questionnaires. Subsequently collected data were analyzed using descriptive analysis and Partial Least Square. The Results of this study concluded that job satisfaction is significant positive effect on organizational commitment and Organizational citizenship behaviour. Other results also indicate that organizational commitment is a significant positive effect on Organizational citizenship behaviour. The implications of this study indicate that the need for efforts to improve satisfaction with co-workers and increasing voluntary participation and support functions of the organization both professionally and social nature.
Keywords: job satisfaction, organizational commitment, and OCB